Nutrient-rich versus nutrient-poor foods for depressed patients based on Iranian Traditional Medicine resources - Mandana Tavakkoli-Kakhki; Saeid Eslami; Malihe Motavasselian (Mashhad University of Medical Sciences, 2015)
Objectives: Considering the positive effects of certain nutrients on depression, increasingly prevalent in the contemporary societies, we investigated the nutritional content of prescribed and prohibited foodstuffs for depressed patients in Iranian Traditional Medicine resources. Materials and Methods: In order to conduct the study, credible sources of Iranian Traditional Medicine were primarily reviewed for the prescribed and prohibited foodstuffs for depressed patients. USDA database, as a well-known and valuable source, was then visited to determine the amount of effective nutrients in each foodstuff. Finally, the obtained amounts were compared with each other in three food groups, namely vegetables, fruits and nuts and also high protein products. Results: In Iranian Traditional Medicine texts, the following are prescribed for depression management: basil, coriander, spinach, lettuce, squash, peppermint, dill, chicory, celery, chard, quince, cucumber, watermelon, grape, peach, pomegranate, banana, apple, currant, pistachio, dried fig, almond, egg, chicken, lamb, and trout; cabbage, eggplant, onion, garlic, broad beans, lentils, and beef, meanwhile, are prohibited. In this regard, the effective nutritional content of these foodstuffs was obtained and then compared in the three food groups. Conclusions: This study revealed that spinach, lettuce, chicory, and squash (vegetables), pomegranate and almond (fruits and nuts) and ultimately trout (high protein products) are the best effective foodstuffs on depressed patients from nutritional content aspect.